TOURISM VILLAGE DEVELOPMENT DURING THE COVID-19 PANDEMIC CASE STUDY IN TEGALWANGI VILLAGE TOURISM VILLAGE DEVELOPMENT DURING THE COVID-19 PANDEMIC CASE STUDY IN TEGALWANGI VILLAGE - Muhamammad Hiqbal Pratama; Fitri Dian Perwitasari; Devi Yuliananda; Freddy Wicaksono; Bastoni; Bayu Arisandi (Ann Publisher, 2024)
Students of Universitas Muhammadiyah Cirebon must take part in Student Work Lectures (KKM) as a form of their service to the community. One of the tasks of KKM group 23 in Tegalwangi village is to create a podcast that incorporates the Ngobras (Informal conversation) program about the tourist village. Chatting, talking, or talking casually is the definition of